Prenatal Exposure to the Great Chinese Famine and Risk of Intracerebral Hemorrhage in Mid-life: Prospective Cohort Study (P18-064-19). (13th June 2019) - Li, Yun; Li, Yanping; Gurol, M Edip; Liu, Yesong; Yang, Peng; Shi, Jihong; Forman, Michele; Wu, Shouling; Gao, Xiang
Abstract: Objectives: The "Developmental Origins of Health and Disease" hypothesis suggests that adversity in early life, particularly in utero, affects health status later in life. We thus investigated whether prenatal exposure to the Great Chinese famine 1959–1961 was associated with risk of intracerebral hemorrhage (ICH) in adulthood. Methods: Included were 97, 399 participants of the Kailuan Study, who were free of stroke, myocardial infarction, or cancer at baseline (2006). Incident ICH cases were confirmed by medical record review. The cox proportional hazards model was used to calculate the hazard ratio (HR) and 95% confidence interval (95%CI) for ICH, according to prenatal famine exposure status. Results: During a median 9.0 years of follow-up (2006–2015), 724 incident intracerebral hemorrhage cases were identified. After adjustment for potential confounders, the hazard ratio (HR) of intracerebral hemorrhage was 1.49 (95%CI: 1.01 to 2.19) for prenatal famine exposed individuals versus individuals born between 1956–1958 and not exposed in utero. When exposure to famine and severity of famine were examined jointly, the adjusted HR was 2.81(95% CI: 1.11 to 7.13) for prenatal exposure to severe famine and 1.81 (95%CI: 1.16 to 2.82) for prenatal exposure to less-severe famine, relative to those without prenatal exposure to famine at all (born between 1956 and 1958). The associations between prenatal exposure and ICH risk were more pronounced in individuals who were overweight or hypertensive, compared to normal weight and non-hypertensives, respectively (P interaction < 0.05 for both). Conclusions: Individuals with prenatal exposure to famine, especially exposed to severe famine, were more likely to suffer from intracerebral hemorrhage in midlife, highlighting the role of nutritional factors in susceptibility to this severe cerebral condition. Funding Sources: This research is supported by the start-up grant from the college of health and human development and the department of nutritional sciences, Penn State University and the Institute for CyberScience Seed Grant Program, Penn State University. Supporting Tables, Images and/or Graphs: